If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = 16 + -2x Solving 4x = 16 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4x + 2x = 16 + -2x + 2x Combine like terms: 4x + 2x = 6x 6x = 16 + -2x + 2x Combine like terms: -2x + 2x = 0 6x = 16 + 0 6x = 16 Divide each side by '6'. x = 2.666666667 Simplifying x = 2.666666667
| 3x-2=7x+17 | | -16t^2+48t-640=0 | | (x+4)(x-6)=7x | | 36-9a^2=0 | | -16p-5(3-4p)=2(p-4)-11 | | 4y^2-24y+20= | | 4y^2-12y-40= | | 3(-3y-3)=-9y+23 | | 11+8x=23 | | 3[4-(-2x-5)]=48x+132 | | 16t^2-140t=68 | | 10+x+14=30+5 | | 16t^2-12ft-182=0 | | 7b= | | -8x-3=4x+9 | | a+4b= | | 2x-8+7= | | 6a+9b= | | 7.3x-3.1=11.5 | | 5t^2-15+2=10 | | 8a+3b= | | X^2+2x=60 | | 7x+5(x+2)+4= | | 3p+5=30p | | 4(logx-1)=18 | | 16x^4+16x^2+3=0 | | 12a+15b= | | (7x-4)(7x+5)= | | 3v+w+8-2v+2= | | -2-17-22=2y+3(y-6) | | -5+(19)+(-34)+44= | | 2x+5x^4+6=0 |